Maldives : 2002 Article IV Consultation-Public Information Notice; Staff Report; and Statement by the Executive Director for Maldives. (IMF Staff Country Reports; Country Report, 2019)
This 2002 Article IV Consultation with Maldives discusses that the performance of the Maldivian economy was strong through most of the past decade, despite handicaps arising from its small size and vulnerability to external developments. The devaluation and the weaker dollar have brought the effective real exchange rate closer to that of main competitors. Reserves have clawed back some of the losses in the aftermath of the devaluation. The 2002 Article IV discussions presented the opportunity to reassess progress toward restoring the soundness of macroeconomic and structural policies. In order to ensure a favorable medium-term performance for the Maldives, policies need to support the fixed exchange rate and adapt to ongoing structural changes-notably, the progressive liberalization of the financial sector, further private sector participation in activities still dominated by state-owned enterprises, and the likely tapering off of external assistance. The authorities have made some progress in responding to key policy challenges. Recent consultations have stressed the need for a stronger fiscal position and independent monetary management.